Literature Review: The Effect of Virtual Laboratories on Students' Motivation and Learning Interest - Baiq Oriza Januarlinda; Nurul Asmaya Fitria Hasanah; Baiq Anisya Nelahi Purnadya; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2024)
This systematic literature review aims to examine the effectiveness of virtual laboratory implementation in enhancing students’ motivation and interest in learning based on scientific articles published between 2015 and 2024. A total of 17 empirical studies were analyzed using a qualitative descriptive content analysis method. The articles were collected through a systematic search using the Publish or Perish application in the Google Scholar and OpenAlex databases with the keywords: “virtual laboratory,” “virtual lab,” “PhET simulation,” “learning motivation,” and “learning interest.” Most of the analyzed studies were conducted at the junior and senior high school levels (SMP and SMA). The results indicate that all analyzed studies (100%) reported a positive effect of virtual laboratories on students’ affective domains, reflected in increased motivation scores and learning interest. PhET Simulation emerged as the most widely used platform (52.94%), particularly in Physics topics such as Archimedes’ Law, Heat and Temperature, and Harmonic Motion. Publication trends showed a significant peak in 2022 (29.41%), corresponding to the accelerated adoption of digital learning technologies during the post-COVID-19 era. The findings suggest that the effectiveness of virtual laboratories is driven by dynamic visualization of abstract concepts, interactive feedback, and flexibility in conducting repeated experiments. Overall, the findings indicate that virtual laboratories are effective learning media for improving students’ motivation and interest, particularly at the junior and senior high school levels. Their effectiveness is further supported by the integration of appropriate instructional models and the teacher’s role as a facilitator.